Hierarchically organized materials with ordered mesopores: adsorption isotherm and adsorption-induced deformation from small-angle scattering. Issue 22 (28th May 2020) - Ludescher, Lukas; Morak, Roland; Braxmeier, Stephan; Putz, Florian; Hüsing, Nicola; Reichenauer, Gudrun; Paris, Oskar
Abstract : Apparent strain artifacts resulting from the evaluation of small-angle X-ray scattering data superimpose the actual adsorption induced deformation in silica with hierarchical porosity. These artifacts can be corrected for by detailed modelling. Abstract : In situ small angle scattering is used to study the pore filling mechanism and the adsorption induced deformation of a silica sample with hierarchical porosity upon water adsorption. The high structural order of the cylindrical mesopores on a 2D hexagonal lattice allows obtaining adsorption induced strains from the shift of the corresponding Bragg peaks measured by in situ small-angle X-ray scattering (SAXS). However, apparent strains due to scattering contrast induced changes of the Bragg peak shapes emerge in SAXS. In contrast, small-angle neutron scattering (SANS) allows determining the real adsorption induced strains by employing a H2 O/D2 O adsorbate with net coherent scattering length density of zero. This allows separating the apparent strains from the real strains experimentally and comparing them with strains obtained from model calculations of the SAXS intensity. It is shown that the apparent strains cannot be described at all by a simple mesopore model of film growth and capillary condensation. A hierarchical model taking the scattering of the micropores and the outer surface of the mesoporous struts in the hierarchically porous sample properly into account, together with a modified mesopore filling mechanism based on a corona model, leads to satisfactory description of both, the adsorption isotherm and the measured apparent strains as derived by SAXS.